Uji Kinerja Pencacah Porang - Warji, Warji; Novita, Dwi Dian; Rahmawati, Winda (Jurnal Agricultural Biosystem Engineering, 2022)
Porang is a type of tuber that is widely cultivated because of its high economic value. Porang tubers have good prospects to be developed as main and functional food ingredients. Processed porang tubers include porang chips, imitation rice, porang noodles, jelly and other preparations. One of the important processing of porang is the process of making porang tuber chips. Porang tuber chips can be made using a chopper machine. This study aims to test the performance of the porang tuber chopper machine. The research includes the theoretical test of the chopper machine and the actual test of the porang tuber chopper machine. The efficiency and effectiveness of the chopper also determinted. With the existence of an effective and efficient chopper machine, it can help farmers to chop porang tubers into porang tuber chips. Porang tuber chips have a higher economic value than porang tubers; with the chopper machine is expected to increase the income of porang farmers. The actual working capacity of the machine is 115kg/hour, the theoretical working capacity of the machine is 226 kg/hour and 78% for the large part and 74% for the small part, the thickness of the slices produced ranges from 3-8 mm; reached 85%.